THE ROLE OF MONITORING OF INTRACRANIAL PRESSURE IN ESTIMATION OF CLINICAL SYMPTOMS AND PROGNOSIS OF RESULTS OF TREATMENT IN CHILDREN WITH SEVERE CRANIOCEREBRAL INJURY - O.S. Iskhakov ("Paediatrician" Publishers LLC, 2009)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):148-149)